DO FINANCIAL AND NON-FINANCIAL FACTORS AFFECT SUSTAINABLE GROWTH RATES? - Huda, Nurul; Kholilah, Kholilah (Jurnal Akuntansi Kontemporer, 2025)
Research Purposes. This study aims to identify the effect of profitability, leverage, firm size and sustainable report disclosure on sustainable growth rate. Research Methods. This research is quantitative research with exploratory type, panel data analysis is used to test the hypothesis. This research was conducted on 29 companies engaged in energy, basic materials, and infrastructure listed on the IDX during the 2020-2023 period. Research Results and Findings. The results of this study indicate that sustainable report disclosure and profitability negatively affect the sustainable growth rate. At the same time, leverage and company size do not affect the sustainable growth rate.  Therefore, the results of this study can be used as a basis for decision-making and preparation of financial and operational strategies to support sustainable company growth. In addition, this study provides a new perspective for investors in assessing and selecting companies with high sustainable growth rates as investment options.